An Appraisal of Nigeria’s Micro, Small and Medium Enterprises (MSMES) - Ebitu; Tom, Ezekiel; Glory; Ufot Juliet Alfred, Basil (British Journal of Marketing Studies, 2016)
This paper took a critical appraisal of the Micro, Small and Medium Enterprises (MSMEs) in Nigeria. The major focus of this work was to expatiate on the growth, challenges and prospects of the MSMEs in the country. While attempting to give an appropriate definition for Micro, Small and Medium Enterprises using employment strength and asset base criteria, the work revealed that SMEs contribute significantly to economic development in the provision of goods and services, creation of employment and contribute to a high standard of living. There are some setbacks facing the over 17,284,671 Micro, Small and Medium Enterprises in Nigeria. These setbacks include; limited financing, lack of action plan to deal with eventualities, lack of managerial and marketing skill, and lack of research appreciation and technical expertise. The study concluded that entrepreneurship is regarded as the catalyst in most developing economies and that it is very crucial to the economic growth and development of Nigeria. As such, it was recommended that government policies should support the establishment, nurturing and growth of SMEs by curtailing or banning importation of certain products, training of young entrepreneurs, establishment of Centers for Entrepreneurial Development and promoting entrepreneurial spirit through the provision of conducive entrepreneurial environment, funding and empowerment programmes. This will facilitate the training and retraining of entrepreneurs and also help Nigerian youths to develop interest in entrepreneurship.